2010
DOI: 10.1111/j.1365-2648.2010.05342.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing heart failure patients’ sleep quality

Abstract: Patients with heart failure should be taught sleep hygiene and to increase leisure time activities, disease self-management, and emotional adjustment skills to improve their sleep quality. These patients should also be observed for night time safety risk due to nocturia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
92
3
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(124 citation statements)
references
References 27 publications
13
92
3
16
Order By: Relevance
“…Among "bad sleepers", it was the second most frequent report, together with being unable to sleep within 30 minutes (77.7%) ( Table 1). These results are compatible with those found in other studies involving samples of HF patients in various functional classes, without stratification, in which 78.2% (13) or 83.2% (12) of HF patients studied reported getting up at night to go to the bathroom as a difficulty to continue sleeping. Although its mechanism is not well understood, nocturia can be triggered not only by rest and other conditions in which the blood volume is dislocated to central body regions, but also by sleep apnea, involving the hormone system of sodium and water control (21) .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Among "bad sleepers", it was the second most frequent report, together with being unable to sleep within 30 minutes (77.7%) ( Table 1). These results are compatible with those found in other studies involving samples of HF patients in various functional classes, without stratification, in which 78.2% (13) or 83.2% (12) of HF patients studied reported getting up at night to go to the bathroom as a difficulty to continue sleeping. Although its mechanism is not well understood, nocturia can be triggered not only by rest and other conditions in which the blood volume is dislocated to central body regions, but also by sleep apnea, involving the hormone system of sodium and water control (21) .…”
Section: Discussionsupporting
confidence: 82%
“…These results are similar to findings in another study of HF patients (13) , who mentioned that they did not sleep enough or did not have enough energy to work when they woke up the next morning. In general, sleeping problems cause fatigue, concentration loss and excessive sleepiness (12) .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…21 In this study, it was reported 3 patients (6%) expressed palpitation and 8 patients (16%) expressed irritability/agitation. This study results supports the other studies in the literature about effects of noise on sleep.…”
Section: Discussionmentioning
confidence: 54%